Grappling With Complexity in Research with the Military Police The Far-Right and Anthropology’s Civilizing Mission - Tomás Salem (Vibrant: Virtual Brazilian Anthropology)
Abstract: This text examines the challenges of carrying out fieldwork with the Military Police, an institution responsible for systematically targeting Rio de Janeiro’s favela populations with extreme levels of racialized state violence. It discusses how anthropologists can describe police officers in ways that avoid the pitfalls of binary thinking: of reproducing a cosmology of war that assumes a strict division between good and evil and instead produce accounts that hold space for complexity and change, without assuming a moral relativist position.